Epigenetic approaches by analysis of circulating miRNAs and global DNA methylation in veterinarians occupationally exposed to volatile anesthetics - Tony Fernando Grassi; Mariane Aparecida Pereira Silva; Maria Vitória Destro; Iael Weissberg Minutentag; Patrícia Pintor Reis; Bruno Spinosa De Martinis; Mónica Cappetta; Leandro Gobbo Braz; Mariana Gobbo Braz (Toxicology, 2026)

Water pollution caused by ash from grassland fires alters the molecular, biochemical, and morphological biomarkers of non-biting midge larvae - Ronnilda Maria Gonçalves Araujo; Ana Marta Schafaschek; Cinara Wanderléa Felix Bezerra; Diego José Nogueira; Marco Tadeu Grassi; Mario Antonio Navarro-Silva; Bruno Renaly Souza Figueiredo (Journal of Hazardous Materials, 2025)

Environmental and biological measurements of the anesthetic isoflurane and its possible toxic effects in veterinarians - Tony F. Grassi; Mariane A.P. Silva; Maria V. Destro; Bruno S. De Martinis; Leandro G. Braz; Mariana G. Braz (Environmental Toxicology and Pharmacology, 2025)

A novel pathogenic mutation in the ATP5MC3 gene of ATP synthase causing dystonia is associated with autophagic and lysosomal alteration - Clarissa Gissi; Elisa Zamprogno; Marina Comelli; Francesca D’Este; Federico Caicci; Bruno Grassi; Michela Carraro; Paolo Bernardi; Michael Zech; Giovanna Lippe; Camilla Bean (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Effects of 3-month high-intensity interval training vs. moderate endurance training and 4-month follow-up on fat metabolism, cardiorespiratory function and mitochondrial respiration in obese adults - Filippo Vaccari; Angelina Passaro; Andrea D’Amuri; Juana Maria Sanz; Francesca Di Vece; Eleonora Capatti; Benedetta Magnesa; Marina Comelli; Irene Mavelli; Bruno Grassi; Federica Fiori; Giulia Bravo; et al. (European Journal of Applied Physiology, 2020)

A 35-day bed rest does not alter the bilateral deficit of the lower limbs during explosive efforts - Enrico Rejc; Pietro Enrico di Prampero; Stefano Lazzer; Bruno Grassi; Bostjan Simunic; Rado Pisot; Guglielmo Antonutto; Marco Narici (European Journal of Applied Physiology, 2015)

Maximal explosive power of the lower limbs before and after 35 days of bed rest under different diet energy intake - Enrico Rejc; Pietro Enrico di Prampero; Stefano Lazzer; Bruno Grassi; Bostjan Simunic; Rado Pisot; Guglielmo Antonutto; Marco Narici (European Journal of Applied Physiology, 2015)

Acute respiratory muscle unloading by normoxic helium–O2 breathing reduces the O2 cost of cycling and perceived exertion in obese adolescents - Desy Salvadego; Alessandro Sartorio; Fiorenza Agosti; Gabriella Tringali; Alessandra Patrizi; Antonella Lo Mauro; Andrea Aliverti; Bruno Grassi (European Journal of Applied Physiology, 2015)

Skeletal muscle oxygen uptake in obese patients: functional evaluation by knee-extension exercise - Stefano Lazzer; Desy Salvadego; Simone Porcelli; Enrico Rejc; Fiorenza Agosti; Alessandro Sartorio; Bruno Grassi (European Journal of Applied Physiology, 2013)

Isometric strength training lowers the O2 cost of cycling during moderate-intensity exercise - Jerzy A. Zoladz; Zbigniew Szkutnik; Joanna Majerczak; Marcin Grandys; Krzysztof Duda; Bruno Grassi (European Journal of Applied Physiology, 2012)

Slow $$ \dot{V}{\text{O}}_{2} $$ kinetics during moderate-intensity exercise as markers of lower metabolic stability and lower exercise tolerance - Bruno Grassi; Simone Porcelli; Desy Salvadego; Jerzy A. Zoladz (European Journal of Applied Physiology, 2011)

Insights into central and peripheral factors affecting the “oxidative performance” of skeletal muscle in aging - Alessandra Ferri; Saverio Adamo; Miriam Longaretti; Mauro Marzorati; Francesca Lanfranconi; Antonietta Marchi; Bruno Grassi (European Journal of Applied Physiology, 2007)

Neuromuscular recovery after a strength training session in elderly people - Alessandra Ferri; Marco Narici; Bruno Grassi; Michel Pousson (European Journal of Applied Physiology, 2006)

Oxygen uptake kinetics: old and recent lessons from experiments on isolated muscle in situ - Bruno Grassi (European Journal of Applied Physiology, 2003)

Early effects of exercise training on $$ \mathop V\limits^ · {\rm O}_2 $$ on- and off-kinetics in 50-year-old subjects - Yoshiyuki Fukuoka; Bruno Grassi; Marco Conti; Daniela Guiducci; Monica Sutti; Claudio Marconi; Paolo Cerretelli (Pflügers Archiv - European Journal of Physiology, 2002)

A New Specific Enzyme Immunoassay Allowing an Efficient Pharmacokinetic Evaluation of γ-Cyclodextrin After Intravenous Administration to Rats - Christophe Créminon; Florence Djedaïni-Pilard; Raymond Vienet; Christophe Péan; Jean-Marc Grognet; Jacques Grassi; Bruno Perly; Philippe Pradelles (Pharmaceutical Research, 1999)